2010
DOI: 10.1088/0266-5611/26/10/105004
|View full text |Cite
|
Sign up to set email alerts
|

A discrepancy principle for Poisson data

Abstract: In applications of imaging science, such as emission tomography, fluorescence microscopy and optical/infrared astronomy, image intensity is measured via the counting of incident particles (photons, γ-rays, etc). Fluctuations in the emission-counting process can be described by modeling the data as realizations of Poisson random variables (Poisson data). A maximum-likelihood approach for image reconstruction from Poisson data was proposed in the mid-1980s. Since the consequent maximization problem is, in genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
156
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(161 citation statements)
references
References 33 publications
4
156
0
1
Order By: Relevance
“…We denote this error ρ w (for sake of completeness, we point out that we enumerate the pixels from 1 to 1024 in both directions). As previously mentioned, in practical applications, only an estimate of β opt can be obtained (see Bertero et al 2010;Bardsley & Goldes 2009). Moreover, the numerical experience (see Benfenati & Ruggiero 2015) has shown that these methods cannot provide satisfactory results for some classes of images (such as the image treated in this work) because of the hypothesis underlying these techniques.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We denote this error ρ w (for sake of completeness, we point out that we enumerate the pixels from 1 to 1024 in both directions). As previously mentioned, in practical applications, only an estimate of β opt can be obtained (see Bertero et al 2010;Bardsley & Goldes 2009). Moreover, the numerical experience (see Benfenati & Ruggiero 2015) has shown that these methods cannot provide satisfactory results for some classes of images (such as the image treated in this work) because of the hypothesis underlying these techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The parameter β is named regularization parameter and it measures the trade-off between f 0 and f 1 . In practical application, one needs the value that gives the best reconstruction, but actually this value is very difficult to estimate (see Bertero et al 2010;Bardsley & Goldes 2009, for the Poisson case).…”
Section: Generalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The two first terms corresponds to the data fidelity component related to the Poisson statistic , Bertero et al [2010]). The third term is the total variation function (Rudin et al [1992]) which allows to smooth homogeneous areas of the recovered images while preserving sharp edges.…”
Section: Jmap Criterionmentioning
confidence: 99%
“…FISTA is an acceleration procedure for non constraint algorithms [5], and in the special case of the TV functional and ℓ 1 , additional constraints such as the positivity of the solution can be addressed [4]. The choice of the parameter λ in the regularization term was studied in [6] for data fidelity terms issued from a Poisson noise. In [13] an algorithm which belongs to primal-dual methods is described since primal and dual variables are successively computed in the algorithm.…”
Section: Incorporating Noisementioning
confidence: 99%